O gênero discursivo notícia: prática de escrita e leitura mediada por sequências didáticas em turma do 3º ano do ensino fundamental - Santana, Cristiane Maria da Silva (2016)
The present dissertation shows the results of the research carried out in the third stage of the literacy cycle, precisely in the 3rd year of elementary school. The main objective was to describe the production process written from the genre discursive news, analyzing how much its structural characteristics. With this investigation of applied and interventionist character we proposed the development of activities that contributed to the production of the discursive news genre, considering the situational context and its linguistic - discursive characteristic. Basically we support our theoretical construct in Bakhtin (2011), with regard to the conception of discursive genres. As for the news genre, we are guided by the studies carried out by Nascimento (2009). Regarding the methodology, we are based on the modules of Lopes-Rossi (2012) with adaptation of some steps and activities. We also highlight authors who contributed to the understanding of the process in reading and writing in learning; Solé (1999), Koch and Elias (2010), among others. Twelve students participated in the study, being chosen 10 productions for analysis of the corpus. In the first analysis, we identified the difficulties regarding the interaction with the genre, its production and the structural aspects of the genre, especially the production of the title and the lead. Based on the data, we elaborated the didactic sequence with the objective of meeting the needs related to the production process. After the intervention process through the didactic sequence modules, we verified that the participating students presented a significant advance, that is, the second production met our expectations. The results show that classroom work through a didactic sequence contributes to the learning process, as well as solving some problems that interfere with written production.